Religion, Radicalism and National Character: In Perspective of South Sulawesi Local Wisdom - Mahmuddin Mahmuddin (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
It is widely believed that Indonesia is encountering an issue of disharmony due to a number of horizontal conflicts which are based on ethnics, religions, and races. In addition, there are many social issues also happen in recent years that stimulate the conflicts. For example, the rampant of drugs users across the country and the increase of significant number of terrorists in many regions in Indonesia. The writer believes that one of the main reasons of these conflicts is lacking of understanding nation charachter as well as local wisdoms that owned by certain community. In the mean time, Indonesia as country is rich of characters that can unite community under the flag of nation and diminish conflicts among them. In the context of South Sulawesi region, there are, at least, three different characters that can decrease the emergence of radicalism. Firstly, respect to the difference. Secondly, they are open-minded. Thirdly, maintaining tradition of ashame (siri) as a local genius. These characters are social capitals of South Sulawesi communities in tackling radicalism understanding. The writer come to conclude that if every single ethnics in Indonesia make their local genius as their philosophy in daily life, the radicalism movement might be tackled across the country.[Dipercaya secara luas bahwa Indonesia menghadapi masalah ketidakharmonisan karena sejumlah konflik horizontal yang didasarkan pada etnis, agama, dan ras. Selain itu, ada banyak masalah sosial juga terjadi dalam beberapa tahun terakhir yang merangsang konflik. Misalnya, merajalela pengguna narkoba di seluruh negeri dan meningkatnya jumlah teroris yang signifikan di banyak wilayah di Indonesia. Penulis percaya bahwa salah satu alasan utama dari konflik ini adalah kurangnya pemahaman tentang karakter bangsa dan juga kearifan lokal yang dimiliki oleh masyarakat tertentu. Sementara itu, Indonesia sebagai negara kaya akan karakter yang bisa menyatukan masyarakat di bawah bendera negara dan mengurangi konflik di antara mereka. Dalam konteks wilayah Sulawesi Selatan, setidaknya ada tiga karakter berbeda yang dapat menurunkan kemunculan radikalisme. Pertama, hargai perbedaannya. Kedua, mereka berpikiran terbuka. Ketiga, menjaga tradisi ashame (siri) sebagai jenius lokal. Karakter ini adalah ibu kota sosial masyarakat Sulawesi Selatan dalam mengatasi pemahaman radikalisme.  Penulis kemudian menyimpulkan bahwa jika setiap etnis di Indonesia membuat jenius lokal mereka sebagai filosofi mereka dalam kehidupan sehari-hari, gerakan radikalisme dapat ditangani di seluruh negeri.]